Extracellular matrix micropatterning technology for whole cell cryogenic electron microscopy studies. (26th September 2019) - Engel, Leeya; Gaietta, Guido; Dow, Liam P; Swif, Mark F; Pardon, Gaspard; Volkmann, Niels; Weis, William I; Hanein, Dorit; Pruitt, Beth L
Abstract: Cryogenic electron tomography is the highest resolution tool available for structural analysis of macromolecular organization inside cells. Micropatterning of extracellular matrix (ECM) proteins is an established in vitro cell culture technique used to control cell shape. Recent traction force microscopy studies have shown correlation between cell morphology and the regulation of force transmission. However, it remains unknown how cells sustain increased strain energy states and localized stresses at the supramolecular level. Here, we report a technology to enable direct observation of mesoscale organization in epithelial cells under morphological modulation, using a maskless protein photopatterning method (PRIMO) to confine cells to ECM micropatterns on electron microscopy substrates. These micropatterned cell culture substrates can be used in mechanobiology research to correlate changes in nanometer-scale organization at cell–cell and cell-ECM contacts to strain energy states and traction stress distribution in the cell.